Anthropometric Indices and Metabolic Dysfunction–Associated Fatty Liver Disease in Males and Females Living With Severe Obesity - Fannie Lajeunesse-Trempe; Selena Dugas; Ina Maltais-Payette; Ève-Julie Tremblay; Marie-Eve Piché; Georgios K. Dimitriadis; Annie Lafortune; Simon Marceau; Laurent Biertho; André Tchernof (Canadian Journal of Gastroenterology and Hepatology, 2025)
Conclusions: MAFLD and MASH are highly prevalent in individuals living with severe obesity, but no anthropometric indices or laboratory tests are good predictors of MAFLD or MASH in this population. When MAFLD is diagnosed, our results suggest that females with severe obesity might be at higher risk of advanced stages of fibrosis.